Synthesis and characterization of copper complexes with a series of tripodal amine ligands - Mehlich, Frank; Roberts, Asha E.; Kerscher, Marion; Comba, Peter (Inorganica chimica acta, 2019)
A series of copper complexes with tripodal amine ligands was synthesized and structurally characterized. The copper(I) complexes of this series were investigated in regard to their reactivity towards dioxygen using stopped-flow techniques. For most complexes no “dioxygen adduct” complexes as intermediates could be detected. During the course of our investigations it was observed that the copper(II) complex with the ligand 3,3′-dimethylaminopropyl-(2-methylenpyridyl)-amine (Me4-p33) crystallized as a dinuclear complex, [Cu(Me4-p3H3)OH]2(ClO4)4, that could be structurally characterized. Interestingly, it turned out that in crystalline form the two bridging hydroxide ions were intact while two of the amine arms of the two ligands were protonated. DFT calculations were performed to get a better understanding of the behavior of this complex system in solution. Further protonation of two more amine ligand arms in solution was possible, still keeping the bridging hydroxide ions in place in the solid state. A related copper(II) complex system could be crystallized that contained a coordinated carbonate anion together with a protonated amine arm.
Available online 22 November 2018
Gesehen am 15.02.2019